(untitled) (Journal of the Sociology and Theory of Religion, 2014)
Finding sacred space in an urban world, a crowded city such as Accra, can be a daunting task for emerging and established religious groups. Some prayer groups in Accra surmount this hurdle in creative ways such as worshipping in the forest. Leaders and members of informal prayer groups gather at Achimota Forest in Accra daily, except Sundays, with more than 1,000 worshippers on a typical Saturday. Prayer group members have transformed the forest from a recreational park, its intended purpose, into sacred space. This paper investigates how the forest fulfils the need for a place for self-expression and individual attention to personal problems in a sacred space that allows believers to transcend denominations in the expression of their common religious beliefs and practices.